PENGARUH OCB DAN KOMITMEN TERHADAP KINERJA PERANGKAT DESA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Hidayah, Noor; Indaryani, Mamik; Utomo, Joko (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2024)
This research aims to analyze the influence of OCB and Commitment on the Performance of Village Officials with Job Satisfaction as an Intervening Variable (Study on Village Officials throughout Jati District, Kudus Regency). The research sample was 105 respondents. The type of data used is quantitative data, the data source comes from primary data in the form of a questionnaire. Data analysis includes validity tests, EVE (Variance Extracted), Dircrimiunant Validity, and Construct Reliability. Data analysis used is Structural Equation Modeling (SEM) which is operated through the AMOS program. The conclusions of this research include that OCB has a positive and significant effect on Job Satisfaction, Commitment has a positive and significant effect on Job Satisfaction, OCB has a positive and significant effect on Device Performance, Commitment has a positive and significant effect on Device Performance, Job Satisfaction has a positive and significant effect on Village Device Performance throughout Jati District, Kudus Regency.